The impact of overweight and obesity on health-related quality of life in childhood - results from an intervention study - Ravens-Sieberer Ulrike; Petersen Christiane; Erhart Michael; Wille Nora (BMC, 2008)
Abstract Background The negative impact of overweight (including obesity) and related treatment on children's and adolescents' health-related quality of life (HRQoL) has been shown in few specific samples thus far. We examined HRQoL and emotional well-being in overweight children from an outpatient treatment sample as well as changes of these parameters during treatment. Methods In a cross-sectional design, self-reported HRQoL of 125 overweight (including obese) children who contacted a treatment facility, but had not yet receive treatment, were compared to 172 children from randomly selected schools using independent two-sample t-tests. Additionally, in a longitudinal design, the overweight children were retested by administering the same questionnaire at the end of the intervention (after one year). It included measures such as the body mass index (BMI), the general health item (GHI), the KINDLR, and the Child Dynamic Health Assessment Scale (ChildDynHA). Comparisons were based on dependent t-tests and the Wilcoxon signed-rank test. Results Overweight children showed statistically significant impairment in the GHI (Cohen's d = 0.59) and emotional well-being (ChildDynha) (d = 0.33) compared to the school children. With respect to HRQoL, the friends dimension of the KINDLR was significantly impaired in the overweight group (d = 0.33). However, no impairment was found for the total HRQoL score or other KINDLR subdimensions. Regarding the longitudinal part of our study, most of the children improved their BMI, but the majority (87.5%) remained overweight. Nevertheless, the participants' perceived health, emotional well-being, and generic as well as disease-specific HRQoL improved during intervention. Conclusion The findings emphasize the importance of patient-reported outcomes such as HRQoL. Even though overweight and obesity might accompany most of the children throughout their lifetime, the impairment associated with this chronic condition can be considerably reduced. Opportunities of health promotion in overweight/obese children and adolescents are discussed.